Diversifikasi Hasil Perikanan menjadi Berbagai Olahan Pangan Bagi Kelompok PKK Kampung Enam, Kota Tarakan - Kartina, Kartina; Nurhikma, Nurhikma; Dyta Nugraeni, Christine; Alawiyah, Tuty; Gandri Haryono, M.; Sanda Lembang, Miska; Sumarlin, Sumarlin; Gaffar, Syamsidar; Pramita Dewi, Dena; Rahayu, Yane (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
Tarakan City is one of the cities which is famous for its fishery potential. Utilization of fishery products in an efficient and integrated manner is necessary, because fishery products are very susceptible to damage or deterioration of quality so that proper handling is needed, for example through diversification into various processed products. This activity is intended to provide knowledge and skills to PKK group as motivators in the community. This activity was held on Friday, February 7, 2020 which was attended by 40 participants. Activities consist of delivering materials and demonstrations of the manufacture of processed fish and shrimp products. The result of the activity is an increase in the skills and knowledge of the participants in the diversification of various fishery products into nutritious food. Given the great benefits of this activity, it is necessary to conduct similar training to the PKK group regarding packaging techniques so that the products produced can be marketed